WEBVTT
00:00:02.150 --> 00:00:14.700
In a geometric sequence, and for a certain π, we have π sub π equals six, π sub π plus one equals three, and π sub two π minus one equals three-eighths.
00:00:15.120 --> 00:00:18.920
Find the first three terms of the sequence and what π is.
00:00:19.020 --> 00:00:29.170
In this question, weβre told that we have a geometric sequence, and thatβs a sequence where there is a fixed ratio between successive terms.
00:00:29.820 --> 00:00:39.140
Letβs recap a little bit of the notation around geometric sequences, beginning with the fact that we can note each term in terms of its index.
00:00:39.500 --> 00:00:47.800
For example, the first term can be written as π or π sub one, the second term as π sub two, and the third term as π sub three.
00:00:48.280 --> 00:01:02.250
And in a geometric sequence because we multiply any term by π to find the next term, then we could also write that the terms could be written as π then ππ then ππ squared, and so on.
00:01:02.710 --> 00:01:19.100
This leads us into the πth term formula for geometric sequence: π sub π is equal to π times π to the power of π minus one, where π is the index, π is the first term, and π is the fixed ratio between terms.
00:01:19.630 --> 00:01:24.020
So, letβs have a look at what weβre told about the terms of this sequence.
00:01:24.630 --> 00:01:31.640
The first piece of information weβre given is that for a certain value of π we have π sub π is equal to six.
00:01:31.860 --> 00:01:35.320
So, somewhere in this sequence there is a term six.
00:01:36.030 --> 00:01:45.600
Weβre then given another term, π sub π plus one is equal to three, so we know that somewhere in this sequence there will be a term three.
00:01:46.160 --> 00:01:51.610
However, π sub π plus one is the term that comes immediately after π sub π.
00:01:51.810 --> 00:01:56.710
And so, we know that three must come immediately after the term six.
00:01:57.390 --> 00:01:59.370
Weβre then given a third term.
00:01:59.630 --> 00:02:02.950
π sub two π minus one is equal to three eighths.
00:02:03.380 --> 00:02:10.420
We donβt know exactly where this fits in relation to the two other given terms, so letβs just note that itβs somewhere else in the sequence.
00:02:11.050 --> 00:02:16.990
Now, letβs see if we can write these three terms in a way that relates π and π.
00:02:17.600 --> 00:02:24.470
We can write the first of our given terms π sub π as π times π to the power of π minus one.
00:02:24.930 --> 00:02:30.870
The next term π sub π plus one can be written as π times π to the power of π.
00:02:31.250 --> 00:02:37.500
Remember that this comes from the fact that the exponent of π must be one less than the index.
00:02:38.150 --> 00:02:46.240
The final given term π sub two π minus one can be written as π times π to the power of two π minus two.
00:02:46.990 --> 00:02:50.320
At the minute, we have a lot of unknowns in this question.
00:02:50.610 --> 00:02:57.220
However, we can work out the value of π given that we have two successive terms in the sequence.
00:02:57.860 --> 00:03:09.890
In a geometric sequence, because we could take any term and multiply it by the fixed ratio to get the next term, then we can ask ourselves, what must we multiply six by to get three?
00:03:10.490 --> 00:03:12.300
Well, it must be one-half.
00:03:12.480 --> 00:03:17.430
And so, we have our first piece of information that π is equal to one-half.
00:03:17.980 --> 00:03:31.080
Since we know that π is equal to one-half, we can rewrite π times π to the power of π minus one as π times one-half to the power of π minus one, and we know that it must equal six.
00:03:31.750 --> 00:03:41.100
Then using the fact again that π is equal to one-half, we can write a second equation that π times one-half to the power of π is equal to three.
00:03:41.780 --> 00:03:49.540
We could also write a third equation that π times one-half to the power of two π minus two is equal to three-eighths.
00:03:50.280 --> 00:03:58.400
At the minute, we couldnβt use any single one of these equations to solve since we have two unknowns π and π.
00:03:59.060 --> 00:04:02.610
We can however solve two of these equations simultaneously.
00:04:02.900 --> 00:04:07.250
So, letβs see if we could take any of the equations and write it in terms of π.
00:04:07.840 --> 00:04:13.460
Using the second equation, we could divide through by one-half to the power of π.
00:04:13.930 --> 00:04:26.320
We can write the denominator of this fraction in a nicer way by recognizing that if weβre dividing by a number to the power of π, then thatβs equivalent to multiplying by that number to the power of negative π.
00:04:27.060 --> 00:04:30.560
Now, we have a value for π in terms of π.
00:04:30.900 --> 00:04:34.360
And letβs substitute this into our third equation.
00:04:35.100 --> 00:04:43.770
This gives us three times one-half to the power of negative π times one-half to the power of two π minus two is equal to three-eighths.
00:04:44.390 --> 00:04:56.060
In order to simplify this, we can remember one of the rules of exponents that π to the power of π₯ multiplied by π to the power of π¦ is equal to π to the power of π₯ plus π¦.
00:04:56.480 --> 00:05:04.380
And therefore, when we add the exponents negative π and two π minus two, we get an exponent of π minus two.
00:05:05.150 --> 00:05:08.150
We can then divide both sides by three.
00:05:08.370 --> 00:05:12.430
And three-eights divided by three is three twenty-fourths.
00:05:12.930 --> 00:05:19.530
We can further simplify this to give us one-half to the power of π minus two is equal to one-eighth.
00:05:20.260 --> 00:05:26.180
At this point, there are a number of different ways we could potentially solve this to find the value of π.
00:05:26.680 --> 00:05:32.740
However, perhaps the easiest way is simply to consider the whole exponent as an unknown value.
00:05:33.000 --> 00:05:38.970
And therefore, weβre asking one-half to the power of what would give us one-eighth.
00:05:39.580 --> 00:05:48.970
And in fact, one-half cubed would give us one-eighth since one-half times one-half is one-quarter and one-quarter times one-half is one-eighth.
00:05:49.550 --> 00:05:53.880
And therefore, we can say that this exponent must be equal to three.
00:05:54.070 --> 00:05:56.570
So, π minus two is equal to three.
00:05:56.970 --> 00:05:59.820
And so, π must be equal to five.
00:06:00.590 --> 00:06:07.630
So now weβve worked out the value of π, letβs clear some space and see how this has helped us working out the sequence.
00:06:08.160 --> 00:06:14.110
Given that π is equal to five means that we can say that itβs the fifth term, which is equal to six.
00:06:14.740 --> 00:06:22.740
We can then substitute π is equal to five into this equation, π times one-half to the power of π minus one is equal to six.
00:06:23.300 --> 00:06:25.580
We can then simplify the exponent.
00:06:26.110 --> 00:06:31.030
When we calculate one-half to the power of four, we get one over 16.
00:06:31.730 --> 00:06:37.960
We can then divide both sides by one over 16, which is equivalent to multiplying by 16.
00:06:38.540 --> 00:06:41.230
And six times 16 is 96.
00:06:41.450 --> 00:06:45.040
So now, we know the value π is equal to 96.
00:06:45.660 --> 00:06:49.010
Weβve now found the value of all of the unknowns in this question.
00:06:49.320 --> 00:06:55.930
However, the fact that π is equal to 96 also gives us the first term of the sequence.
00:06:56.410 --> 00:07:00.040
The first term of this sequence must be 96.
00:07:00.630 --> 00:07:07.140
Weβre asked here to find the first three terms, so we need to find the second and third term.
00:07:07.780 --> 00:07:14.430
The second term in the sequence will be given by the first term multiplied by the common ratio π.
00:07:14.770 --> 00:07:21.190
And since 96 multiplied by one-half is 48, then the second term is 48.
00:07:21.790 --> 00:07:25.490
We can work out the third term of this sequence in two different ways.
00:07:25.820 --> 00:07:32.440
The first way is by recognizing that it must be equal to 96 multiplied by one-half squared.
00:07:32.930 --> 00:07:41.680
Or alternatively, we could also realize that to find the third term we take the second term and multiply it by the common ratio of one-half.
00:07:42.190 --> 00:07:45.190
Either way would give us the value of 24.
00:07:45.800 --> 00:07:48.220
We can then give a complete answer.
00:07:48.470 --> 00:07:54.990
We were asked for the first three terms of the sequence, so thatβs 96, 48, 24.
00:07:55.300 --> 00:07:59.780
We were then asked to find the value of π, and so π is equal to five.